Aplicación web móvil para la gestión del departamento de talento humano del ECU 911 de la ciudad de Santo Domingo - Guapi Avimañay, Jessica Verónica (2025)
The purpose of this project is to develop and implement a mobile web application aimed at managing the human resources department at the local operational center of the ECU911 integrated security service in Santo Domingo. The research is based on the principles of transaction processing systems, and this will enable the automation of administrative processes to improve the department's operational efficiency. For its development, specific objectives were established, including the design of functionalities using UML diagrams, the development of the application based on the identified requirements, and the execution of tests to ensure its proper functioning. Among the main functional requirements of the system are user and role management, request administration, document upload, and visualization, as well as the management of employees' vacation information. Additionally, non-functional requirements such as information security, compatibility with different browsers, and portability across various platforms are considered. The implementation of this application will optimize the administration of the human resources department, ensuring better information management and facilitating data analysis for decision-making. This seeks to modernize and streamline internal processes at ECU911 in Santo Domingo, improving the department's accessibility and efficiency. The impact of this project lies in the modernization and automation of the Human Resources department, facilitating access to key information and enhancing decisionmaking. The application will enable better organization of processes, greater efficiency in human resource management, and optimized accessibility from mobile devices. This system represents an innovative tool to enhance the operational efficiency of ECU911 in Santo Domingo, contributing to a faster, more secure, and more efficient administration of human resources within the institution.